THE BAD EFFECTS OF EATING AND DRINKING STANDING IN THE ISLAMIC VIEW - Rayhanu Akram; M Adib Al-Asyrof; Rizky Kurnia Hasibuan; M Reza Al-Fasha (MEDALION JOURNAL: Medical Research, Nursing, Health and Midwife Participation, 2025)
The prohibition of eating and drinking stands in Islam not only related to adab, but also holds profound wisdom that includes aspects of health, simplicity, and spirituality. This article discusses the wisdom contained in the recommendation to eat and drink while sitting based on the views of Islam. One of the main lessons is the importance of maintaining manners in every action as a reflection of the faith of a Muslim. In addition, the habit of eating and drinking calmly while sitting trains modesty, discipline, and increases gratitude to Allah SWT. In terms of health, this habit helps maintain a better digestive process. Thus, following the sunnah of the Prophet PBUH in terms of eating and drinking not only provides spiritual benefits, but also physical benefits. This study confirms that the standing ban on eating and drinking in Islam has a holistic positive impact, covering the physical and spiritual well-being of Muslims.